Pride, shame, and guilt: socio-emotional aspects of the encounter between the Bedouin and Fellahi dialects. Issue 8 (14th September 2021) - Abo-Zaied Arar, Eman; Tannenbaum, Michal
ABSTRACT: This article examines the encounter between two Arabic dialects, one in use in Arab communities in central Israel (originally a community of farmers – Fellahin) and one in use among Bedouins who migrated to the area from the southern Negev area. We relied on semi-structured in-depth interviews with 18 participants representing four Bedouin migrant generations. The findings indicated that Bedouin migrants perceive the Bedouin dialect as a different language, which they have to 'translate' to the local Fellahi population. A clear inter-generational distinction was found in the willingness to switch from the Bedouin to the Fellahi dialect or to mix the two. Migrant parents have more negative feelings about mixing the Bedouin and Fellahi dialects than children who did not experience migration. Linguistically, the first generation exhibited differentiation, hybridity, and a tendency to avoid integration into the local population in an attempt to preserve the Bedouin dialect. This pattern dwindled in subsequent generations – the second tended to adopt an 'intermediate' dialect, whereas the third tends to mix the two and use each one according to the home or public spheres. Further conclusions and implications are also considered.